Towards carbon neutrality: A comprehensive study on the utilization and resource recovery of coal-based solid wastes - Zhiguo Zhang; Cui Xu; Gan Cheng; Ee Von Lau (International Journal of Coal Science & Technology)
Abstract Coal-based soild wastes (CBSWs) are industrial byproducts that can be harmful to the environment. The exploitation and utilization of CBSWs offer societal advantages such as resource conservation, pollution reduction, and cost-effective production. However, environmentally sustainable management remains a worldwide challenge due to the substantial production volume and limited disposal capacity of CBSWs. The physicochemical properties and utilization of CBSWs are summarized, including fly ash, coal gangue and coal gasification slag. It also presents the current global applications status of CBSWs resources and examines market supply and demand. Subsequently, the paper provides an overview of studies on ways to utilise CBSWs, highlighting the primary avenues of CBSWs resource utilization which are mainly from the fields of chemical materials, metallurgy and agriculture. Furthermore, a comparative evaluation of the various methods for CBSWs resource recovery is conducted, outlining their respective advantages and disadvantages. The future development of CBSWs recycling processes is also discussed. The review concludes that while there is a growing need for attention in CBSWs recycling, its utilization will involve a combination of both large-scale treatment and refinement processes. The paper aims to offer references and insights for the effective utilization and environmental protection of CBSWs. Future direction will focus on the collaborative utilization of CBSWs, emphasizing on the combination of large-scale and high-value utilization. In addition, there is a need to establish a comprehensive database based on on-site production practices, explore on-site solutions to reduce transportation costs, and improve physicochemical properties during the production process.